Papillary Thyroid Cancer Metastases to the Parathyroid Gland - Brian O'Sullivan; Tom Burton; Fouzia Ziad; Goswin Meyer Rochow (SAGE Publishing, 2022)
Introduction: Papillary Thyroid cancer (PTC) is the most common malignancy encountered by endocrine surgeons accounting for up to 85% to 90% of all thyroid malignancies. Parathyroid metastases appear to be an uncommon phenomenon however are likely to be underdiagnosed due to routine parathyroid gland preservation during thyroidectomy. Case: We present the case of 63-year-old lady with PTC metastases to the parathyroid gland. She underwent total thyroidectomy, central compartment lymph node dissection and selective left neck (levels IIA-IV) lymph node dissection. Final pathology confirmed a 45 mm low grade conventional type papillary carcinoma with microscopic extension into perithyroidal soft tissue focally and into the adjacent left parathyroid gland. Conclusion: Parathyroid gland thyroid cancer infiltration/metastasis is rarely reported and likely underdiagnosed. This is the first case of parathyroid gland metastasis reported from New Zealand or Australia to our knowledge. There is currently limited research available to guide whether parathyroid gland infiltration or metastasis is of clinical or prognostic significance and whether a more aggressive treatment strategy is warranted when present.